Fitoterapia e essências florais no controle da ansiedade entre docentes do curso de graduação em enfermagem - Zanusso, Carmem Silvia (2019)
Teaching, especially in the health area, involves activities with intense and constant interaction among the most diverse people, which can generate negative impacts, which affect not only the students' expectations. However, it is noticeable that the health of the teacher ends up being the most affected by the negative impacts during the teaching and learning process. Objective: To verify if the phytotherapic Melissa officinalis combined with the Floral Essence Agrimony eupatoria alleviates the anxiety symptoms of teachers of the Undergraduate Nursing Course in a public educational institution.Method: This is a quasi-experimental study, with pre- and post-tests, carried out in the three departments of Nursing at the School of Medicine of São José do Rio Preto - SP. The sample consisted of 30 undergraduate nursing undergraduates, who were submitted to the Beck Scale Anxiety Test (BAI) and rated at the minimum anxiety levels of 0-10 points, light of 11-19 points, moderate of 20-30 points and severe of 31-63 points. In this first phase, after the application of the BAI test and, independently of the classificatory result of anxiety, all the participants took placebo. In the second phase, the BAI test was reapplied and the participants were allocated to two groups: (1) intervention of the phytotherapic Melissa officinalis with the floral essence Agrimony, Agrimônia eupatori and (2) control. In the final phase, the two groups were again submitted to the Beck Scale Anxiety Test (BAI). Results: Anxiety scores, after administration of the medication, decreased in the intervention group when compared to the control group. Conclusion: The combination of the administration of the phytotherapic Melissa officinalies and the floral essence Agrimony eupatoria was effective to reduce anxiety in undergraduate Nursing teachers.